Effectiveness of Pulmonary Tuberculosis Care in Amphoe Mueang, Ranong Province - Jitpratoom, Pornlert (Journal of Health Science of Thailand, 2018)
During 2003-2005, the outcomes of the health care service for pulmonary tuberculosis in Ranong Hospital, the tertiary-care hospital in provincial area of Thailand showed only 54.09-70.13 percent success rate based on the pulmonary tuberculosis population, which failed to follow the guideline of World Health Organization (WHO). Hence, a change to the new method for anti-tuberculosis drugs administration, was called for. In this retrospective descriptive study the OPD card of the 281 patients diagnosed with pulmonary tuberculosis from 1 October 2003 to 30 September 2007 were reviewed. The outcomes of the new and the old programs for pulmonary tuberculosis care service were compared. The results showed the statistical difference (p-value 0.021) between the success rate of in the old program (67.78%) and in the new program (80.92%). The quality of life of the patients 47.17 percent after the new program was classified in a good level and 52.83 percent in a middle level.